Wortmannin Inhibits the Increase in Myofilament Ca2+ Sensitivity Induced by Cross-Talk of Endothelin-1 With Norepinephrine in Canine Ventricular Myocardium - Li Chu; Ikuo Norota; Kuniaki Ishii; Masao Endoh (Elsevier, 2009)
Endothelin-1 (ET-1) modulates cardiac contractility by cross-talk with norepinephrine (NE) in canine ventricular myocardium. The present experiments were performed to investigate the influence of wortmannin that has inhibitory action on phosphatidylinositol 3-kinase (PI3-K) (IC50 = 3 nM) and myosin light chain kinase (MLCK) (IC50 = 200 nM) on Ca2+ signaling and the inotropic effects of ET-1 induced by cross-talk with NE. Experiments were carried out in isolated canine ventricular trabeculae and indo-1/AM-loaded single ventricular cardiomyocytes. ET-1 alone elicited a transient small negative inotropic effect (NIE). In the presence of NE at low (1 - 10 nM) and high (100 nM) concentrations, ET-1 induced a long-lasting positive inotropic effect (PIE) or a marked sustained NIE, respectively. Wortmannin up to 300 nM did not affect the contractility; and at 1 μM and higher, it decreased the basal contraction without suppressing Ca2+ transients. Wortmannin (1 μM) inhibited the long-lasting PIE of ET-1 without affecting the ET-1-induced increase in Ca2+ transients. Wortmannin at the same concentration did not affect the ET-1-induced transient and sustained NIE and the PIE mediated by β-adrenoceptor stimulation. These results imply that wortmannin exerts selective inhibitory action on the increase in myofilament Ca2+ sensitivity induced by cross-talk of ET-1 with NE probably through an inhibition of MLCK in canine ventricular myocardium. Keywords:: inotropic effect, Ca2+ transient, endothelin-1, norepinephrine, wortmannin